Correlation of COVID-19 with severity of periodontitis-A clinical and biochemical study - Rupali Kalsi; Zoya Ahmad; Mallapragada Siddharth; Kharidhi Laxman Vandana; Sachit Anand Arora; Kumar Saurav (Wolters Kluwer Medknow Publications, 2022)
Background: Various conceptual hypotheses have been put forth to link association of COVID-19 with various chronic diseases such as periodontitis. Empirical evidence is still lacking to correlate the severity of COVID-19 with periodontal diseases. Objectives: This study was undertaken with an objective to correlate COVID severity in systemically healthy patients suffering from periodontal diseases. Materials and Methods: 44 systemically healthy patients of both genders with minimum of 20 teeth in their oral cavity in age range of 20 to 50 years suffering from periodontitis were recruited and categorised into four stages as per American Academy of Periodontology (AAP) 2017 classification for periodontitis. Serum C-reactive protein (CRP) levels and periodontal disease parameters of all the patients were measured. Because of COVID-19 and the nationwide lockdown, the dental practice was highly affected. With the help of self-designed online questionnaire information regarding COVID-19 infection and associated symptoms were recorded. Cases were categorized into five groups based on the World Health Organization clinical progression scale of COVID severity. Results: All the patients suffering from COVID disease in moderate and severe forms had increased probing pocket depth, clinical attachment level, and raised serum C-reactive protein levels as compared to patients who were uninfected or suffering from mild COVID disease and the results were statistically significant. Conclusion: Prioritisation and Implementation of periodontal treatment as a preventive measure for COVID-19 should be done. A positive correlation is observed between the severity of periodontitis and COVID-19.